Test Of Antibacterial Activity Of Ethanol Extract Of Maman Lanang Plant (Cleome Rutidospermae Dc ) Against Gram Positive And Negative Bacteria (Staphylococcus aureus and eschericihia coli) - Nurul Furqan, Baiq Repika; Sanjaya, Denny; Almahera, Almahera; Maharani, B Firia (Biota, 2022)
The Maman Lanang plant ( Cleome rutospermae dc ) is a weed plant that is often found in rice fields or grows on community cultivated plants which are usually used as food for people on the outskirts. This research aims to determine the effect of the extract concentration of the Maman Lanang Plant ( Cleome rutospermae dc ) on the inhibition zone for the growth of Staphylococcus aureus and Escherichia coli bacteria, as well as to find out how much the concentration of the extract from the Maman Lanang Plant ( Cleome rutospermae dc ) is close to the inhibitory zone value of the positive control of tetracycline in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria . This research is a laboratory experimental study using a Completely Randomized Design (CRD) using the hole/cup diffusion method with four varying concentrations, namely 10%, 30%, 60% and 90%, and the positive controls used are tetracycline and distilled water as a negative control. The main ingredient used in this research was the Maman Lanang plant ( Cleome rutospermae dc ) which was extracted using the maceration method for three days with 96% ethanol solvent, after that the extract obtained was then subjected to an evaporator to obtain the crude extract then carried out a phytochemical test and after that The antibacterial activity of the crude extract from the Maman Lanang Plant ( Cleome rutospermae dc ) was tested against the bacteria Staphylococcus aureus and Escherichia coli . Then the data obtained was analyzed using the antibacterial ANOVA ( Analysis of variance ) method. The results of this study show that phytochemical test analysis shows the presence of flavonoid compounds in extracts from the Maman Lanang Plant ( Cleome rutospermae dc ). Furthermore, the analysis showed that variations in concentration of the Maman Lanang Plant ( Cleome rutospermae dc ) had an influence on the antibacterial activity of Staphylococcus aureus and Escherichia coli. Where the higher the concentration of the extract, the larger the inhibition zone will be formed. The 90% concentration of the extract showed the largest inhibition zone with a diameter of 23.3 mm.